Honey bees (Hymenoptera: Apidae) of african origin exist in non-africanized areas of the Southern United States: evidence from mitochondrial DNA - Pinto, M. Alice (2010)
Descendents of Apis mellifera scutellata Lepeletier (Hymenoptera: Apidae) (the Africanized honey bee) arrived in the United States in 1990. Whether this was the Þrst introduction is uncertain. A survey of feral honey bees from non-Africanized areas of the southern United States revealed three colonies (from Georgia, Texas, and New Mexico) with a diagnostic African mitochondrial DNA cytochrome b/BglII fragment pattern. To assess maternal origin of these colonies, we developed a primer pair for ampliÞcation of a cytochrome b fragment and sequenced using internal sequencing primers. Samples of the three reported honey bee colonies plus another 42 representing the 10 subspecies known to have been introduced in the United States were sequenced. Of the three colonies, the colonies from Texas and New Mexico matched subspecies of European maternal ancestry, whereas the colony from Georgia was of African ancestry. Contrary to expectations, the mitotype of the latter colony was more similar to that exhibited by sub-Saharan A. m. scutellata than to the mitotypes common in north African A. m. intermissa Maa or Portuguese and Spanish A. m. iberiensis Engel. This Þnding was consistent with anecdotal evidence that A. m. scutellata has been sporadically introduced into the United States before the arrival of the Africanized honey bee from South America.